LATAR BELAKANG DAN MOTIVASI BERWIRAUSAHA PEDAGANG SAYUR DI PASAR INDUK PUSPA AGRO KABUPATEN SIDOARJO - Akbar, Riza Rofiul; Parsudi, Setyo (Berkala Ilmiah AGRIDEVINA, 2016)
The purpose of this study are: to determine andassess the characteristics of vegetable traders in the MarketUp Puspa Agro, to identify and assess the background ofvegetable traders in Market Up Puspa Agro,to identify andassess motivation vegetable vendors at Market Up PuspaAgro, to identify and assess problems of vegetable traders inMarket Up Puspa Agro.Determining the location of the research was doneintentionally (purposive), which is in the villageof Sidoarjo inEast Java Jemundo. In the area there are Puspa AgroMarket Up as a trading center in East Java Agribusinesscondition is currently experiencing growth or decline, Theconclusion of this study were: male sex Most respondents-male, majoritygreengrocer in Puspa Agro has a brother whotraded vegetables, capital at the greengrocer can come frombank loans, partially greengrocer vegetable tradeexperience, motivation is the most greengrocer to make endsmeet, most of the vegetable vendors are not able to copewith unsoldgoods.Keywords